Cesty horním Kurveleshem v čase a prostoru - Geisler, Adam (Masaryk University Press, 2020)
Title in English: The roads of Upper Kurvelesh through time and space. This publication informs readers about the activities of the archaeological team of the Department of Archaeology and Museology of the Faculty of Arts from Masaryk University in southern Albania. The book also reports on a project marking tourist routes.